2010
DOI: 10.3844/ajessp.2010.449.454
|View full text |Cite
|
Sign up to set email alerts
|

Solar Radiation at Total Solar Eclipse, 29-March 2006, at Tobruq

Abstract: Problem statement: Measurement of the different components of solar radiation and fractions of these components for the global (horizontal and tracker), direct (white and three colors, yellow, red and infrared) and diffuse solar radiation during the solar eclipse, 29 March 2006 at Tobruq, Libya (Lat. 32.08°N and Long. 23.98°E). The time interval of solar eclipse was 2 h: 40 m and the maximum magnitude of eclipse at this region was 0.995. Conclusion: The results showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Measurements of the atmospheric response during the annular solar eclipse of 3 October 2005 have been reported in these regions by [159] in Egypt, and by Anbar (2006) [118] in Saudi Arabia. Also during the total solar eclipse of 29 March 2006, measurements made by Möllman and Vollmer (2006) [160], Uddin et al (2007) [123], Pintér et al (2008), Pleijel (2008) [20] and Stoev et al (2008Stoev et al ( , 2012 [122,161] in Turkey, by Nawar et al (2007) [162] in Egypt, by [119] in Libya and, by Nymphas et al (2009) [163] in Nigeria, were reported. Recently the solar eclipse of 1st September 2016 was observed by Ojobo et al (2017) [146] in Nigeria, and the annular solar eclipse of 26 December 2019 was observed by Nelli et al (2020a) [7] in the United Arab Emirates (U.A.E.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements of the atmospheric response during the annular solar eclipse of 3 October 2005 have been reported in these regions by [159] in Egypt, and by Anbar (2006) [118] in Saudi Arabia. Also during the total solar eclipse of 29 March 2006, measurements made by Möllman and Vollmer (2006) [160], Uddin et al (2007) [123], Pintér et al (2008), Pleijel (2008) [20] and Stoev et al (2008Stoev et al ( , 2012 [122,161] in Turkey, by Nawar et al (2007) [162] in Egypt, by [119] in Libya and, by Nymphas et al (2009) [163] in Nigeria, were reported. Recently the solar eclipse of 1st September 2016 was observed by Ojobo et al (2017) [146] in Nigeria, and the annular solar eclipse of 26 December 2019 was observed by Nelli et al (2020a) [7] in the United Arab Emirates (U.A.E.)…”
Section: Discussionmentioning
confidence: 99%
“…Next is the 29 March mid-day almost total eclipse (99.98%) of 2006 at Tubruq, Lybia (third line in Table 6), near the Mediterranean coast with a background considered to be a desert [119]. The impact on temperature, RH, and VP were also evident but not so large.…”
Section: Previous Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Also, Founda et al [2007] investigated solar radiation variations during the same eclipse in Greece. Later, Hassan and Rahoma [2010] recorded global, direct, and diffuse solar radiation during this event in Tobruq, Libya.…”
Section: Introductionmentioning
confidence: 99%